Efektivitas Program Kantor Urusan Agama dalam Mengurangi Angka Nikah Sirri Tahun 2017-2019 (Studi Kasus KUA Kecamatan Kedungadem Bojonegoro) - M. Ilham Fajry Akbar; Zayad Abd. Rahman; Niwari (MAHAKIM Journal of Islamic Family Law, 2022)
Marriage is an inner and outer bond between a man and a woman as husband and wife to form a happy and eternal family (household) based on God Almighty. Marriage is a legal action, so things or actions that arise as a result of marriage are legal actions that get legal protection. If the marriage is not legally registered, then matters relating to the consequences of marriage cannot be legally resolved. The researcher describes the program from the KUA Kedungadem District in reducing the number of unregistered marriages. File collection methods used are in-depth interviews and documentation techniques. Based on the results of research related to the effectiveness of the Kedungadem Religious Affairs Office program in reducing the number of unregistered marriages in 2017 in terms of time and material, the implementation tends to be effective and successful in reducing the number of unregistered marriages that do not exceed 5 or 0% of unregistered married couples, then in 2018 the time and the implementation was effective and 3 couples did unregistered marriages, so it did not exceed the program target, and then in 2019, this increased to 8 couples who did unregistered marriages so that the program was not successful in reducing the number of unregistered marriages. The program is running and less effective as well as increasing the number of couples who marry sirri. Marriages that meet the requirements and pillars according to religion without being registered at the Office of Religious Affairs are legal enough, but based on regulations in the Indonesian state, marriage is still enforced and is registered in the form of a marriage certificate so that it has legal force. Keywords: The program from Kantor Urusan Agama, Research related to the effectiveness, Reducing the number of unregistered.